Conformational control over π-conjugated electron pairing in 1D organic polymers. Issue 33 (8th June 2021) - Alcón, Isaac; Shao, Jingjing; Tremblay, Jean Christophe; Paulus, Beate
Abstract : Chemically designed conformational changes are shown to act as effective tools to induce electron pairing in otherwise multiradical 1D organic polymers. Abstract : During the past decades π-conjugated bi-radicals have attracted increasing attention, due to the existence of two close-in-energy resonant electronic configurations with very distinct characteristics: the open-shell bi-radical and the closed-shell quinoidal. The chemical design of the bi-radical structure has been shown to be very effective to shift the balance towards one, or the other, electronic distribution. Some reports have experimentally studied the analogous 1D oligomers and polymers, however, only the open-shell multi-radical configuration has been detected, and it is yet not very clear which structural and chemical parameters are relevant in such extended systems. In this work, via first principles quantum chemical simulations, we study a series of π-conjugated 1D polymers based on triarylmethyl radicals with different chemical functionalization. We find that dihedral angles of the aryl rings connecting the radical centres are the key conformational parameter determining the electronic balance. This provides a simple recipe to use chemical functionalization of aryl rings as a tool to shift the system towards either the electron paired or unpaired configurations. Additionally, we find such conformational control is also effective under the effect of thermal fluctuations, which highlights its potential technological applicability.